Kualitas Kayu Meranti Merah (Shorea leprosula Miq.) Hasil Budi Daya - Imam Wahyudi; Julius Johansen Sitanggang (Jurnal Ilmu Pertanian Indonesia, 2017)
Wood quality of five year-old of cultivated Red Meranti (Shorea leprosula Miq.) was studied in order to assure its proper utilization. The evaluation was conducted based on fiber dimension and physical properties of wood. Fiber dimension was measured through maceration specimen, while green moisture content, wood density, and specific gravity were measured following the modification of BS 373.75. Result shows that quality of Red Meranti wood studied was similar to that of naturally grown, except for its fibers which were shorter and thinner than those of naturally grown. It was found that wood quality of each tree was homogenous and even. Result also shows that average values of fiber length, cell wall thickness, moisture content in green condition, wood density and SG are 968.12 µm, 2.72 µm, 104.57%, 0.81 g/cm3, and 0.50, respectively. The wood is categorized as strength class of III, therefore, this Shorea leprosula wood is potential as raw material for plywood and furniture manufacturing, as well as for the 3-rd class of structural and other purposes. The trees unfortunately have not produce the mature wood yet, and the wood produced is not suitable for the highest quality of pulp and paper manufacturing.